Answer:
Step-by-step explanation:
czhnbwbxsbdsc
Add 4 to both sides. Y+4=12x divide both sides by 12 y+4 over 12 which = x switch sides x= y+4 over 12 that’s the answer and I’m 100% sure
Answer:
![x = -4\\x = -3\\x = 3](https://tex.z-dn.net/?f=x%20%3D%20-4%5C%5Cx%20%3D%20-3%5C%5Cx%20%3D%203)
Step-by-step explanation:
To find the real zeros you must match the function to zero and factor the expression.
We have a polynomial of degree 3.
We try to group the terms to perform the factorization
![x ^ 3 + 4x ^ 2-9x-36 = 0\\\\x ^ 2(x + 4) - 9(x + 4) = 0](https://tex.z-dn.net/?f=x%20%5E%203%20%2B%204x%20%5E%202-9x-36%20%3D%200%5C%5C%5C%5Cx%20%5E%202%28x%20%2B%204%29%20-%209%28x%20%2B%204%29%20%3D%200)
Now we take (x + 4) as a common factor
![(x + 4)(x ^ 2 -9) = 0](https://tex.z-dn.net/?f=%28x%20%2B%204%29%28x%20%5E%202%20-9%29%20%3D%200)
If we have an expression of the form
we know that this expression is equivalent to:
![(a ^ 2-b ^ 2) = (a + b)(a-b)](https://tex.z-dn.net/?f=%28a%20%5E%202-b%20%5E%202%29%20%3D%20%28a%20%2B%20b%29%28a-b%29)
In this case
![a = x\\b = 3](https://tex.z-dn.net/?f=a%20%3D%20x%5C%5Cb%20%3D%203)
So:
![(x ^ 2 -9) = (x + 3)(x-3)](https://tex.z-dn.net/?f=%28x%20%5E%202%20-9%29%20%3D%20%28x%20%2B%203%29%28x-3%29)
Finally:
![x ^ 3 + 4x ^ 2-9x-36 = (x + 4)(x + 3)(x-3) = 0](https://tex.z-dn.net/?f=x%20%5E%203%20%2B%204x%20%5E%202-9x-36%20%3D%20%28x%20%2B%204%29%28x%20%2B%203%29%28x-3%29%20%3D%200)
The solutions are:
![x = -4\\x = -3\\x = 3](https://tex.z-dn.net/?f=x%20%3D%20-4%5C%5Cx%20%3D%20-3%5C%5Cx%20%3D%203)
Problem: 2/7 (4+c)=6
1. 7/2 x 2/7 x (4+c)=7/2 x 6
2. 4+c=7 x 3
3. 4+c=21
4. c=21-4
Answer: c=17
1l=1000=>x l=29000000=>x=29000000:1000=>x=29000